Review of the Ulopella leafhopper genus group (Auchenorrhyncha, Cicadellidae, Ulopinae) with description of a new genus and species collected from pitfall traps in Zambia - Smith, Lydia R. J.; Webb, Michael D. (Zootaxa, 2016)
A new ulopine leafhopper genus and species, Kafulopa bicolor gen. nov., sp. n. from Zambia, is described and illustrated and placed in the Ulopella genus group (Ulopini). A checklist and key to the genera of the group are provided together with images of representatives of each genus. Most species of the group are flightless with elytra-like forewings and some, including the new species described here, were collected from baited pitfall traps, suggesting at least a partial association with the soil surface. Aethiopulopa hovana (Lallemand) is re-examined and transferred from the Ulopella group to the Ulopa group (Ulopini), genus Kivulopa comb. nov. and figures of its external features and male genitalia are provided for the first time.